LAW, RELIGION, AND SOCIETY IN CHINA: A CONTESTED TERRAIN. Issue 1 (April 2020) - Mauldin, Joshua T.
Abstract: The tumult of the twentieth century had a great impact on the role of religion in Chinese society. Antipathy toward religion reached its height in China during the Cultural Revolution, one of the few times in history when religion was almost completely wiped out in a single country. Religion in China has experienced a resurgence since the beginning of the Reform and Opening Up period in 1978. With the renewal of religious practice, new proposals have been put forward for the role of religious ideas in public life. In addition to the endurance of Marxist and liberal conceptions of the place of religion in society, new voices have emerged, arguing for return to Confucianism as the source of moral vitality in public life, or advancing Christian public theology as a moral resource for individuals adrift and alienated by the rapid changes of a modernizing economy. These realities have reshaped debates about the protection of religious freedom in China. This article introduces these new social and discursive realities and sets the stage for the articles that follow.